О компактности носителя решения одной эволюционной системы, возникающей из модели Бина в теории сверхпроводимости - Дегтярев, С.П.; Саникидзе, Т.А.; Тедеев, А.Ф. (Видавничий дім "Академперіодика" НАН України, 2007)
The paper deals with an evolutionary degenerate system of the p-Laplacian type which is connected to the known Bean's model in type II superconductivity. For this system which describes the distribution of a magnetic field, we have studied the question of compactness of the support of a solution for finite initial data and external forces. We have obtained an estimate for the support of the solution.